Pengaruh Kewajiban Moral dan Akuntanbilitas Pelayanan Publik Terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan Pada Badan Pajak dan Retribusi Daerah Kota Medan - Elvita Hirani; Alistraja Dison Silalahi (Journal of Trends Economics and Accounting Research, 2020)
The objective of the research was to determine the Effect of Moral Obligations and Accountability of Public Services on Land and Building Taxpayer Compliance with Management Agency Tax and Retribution (BP2RD) in Medan. This research used a quantitative approach. The data source used was primary data with a data collection instrument in the form of a questionnaire. From the result of the research showed that moral obligation partially had a positive and significant effect on compliance with land and building taxpayers, while public service accountability also had a positive and significant effect on land and building taxpayer compliance and simultaneously the moral obligations and accountability of public services had a significant positive effect on compliance with land and building taxpayers.